The impact of government support on the performance of Indonesia's state-owned enterprises - Hendro Nugroho (Asian Development Bank Institute (ADBI), 2019)
This study analyzes the impact of government support on the financial performance of Indonesia's state-owned enterprises (SOEs). I employ the ordinary least square (OLS) method with firm and year fixed effects in addition to clustered standard errors. The findings show that government support for SOEs does not have a significant effect on their financial performance. This study finds that the government should examine its investment policy to support SOEs and consider designing a proper government support policy to generate higher SOE financial performance.
Keywords: G32; G38; H54; 330; state-owned enterprises; government support; government investment; financial performance